Papua New Guinea : 2019 Article IV Consultation and Request for Staff Monitored Program-Press Release; Staff Report; and Statement by the Executive Director for Papua New Guinea. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper presents Papua New Guinea's (PNG) 2019 Article IV Consultation and Request for Staff Monitored Program. The economy is estimated to have rebounded in 2019 following the contraction triggered by the large earthquake in 2018. Inflation is projected to fall in 2019 but to pick up temporarily thereafter. The staff report reflects discussions with the PNG authorities in October 28-November 9, 2019 and is based on the information available as of November 21, 2019. It focuses on PNG near- and medium-term challenges and policy priorities and was prepared before coronavirus disease 2019 became a global pandemic and resulted in unprecedented strains in global trade, commodity and financial markets. It, therefore, does not reflect the implications of these developments and related policy priorities. The outbreak has greatly amplified uncertainty and downside risks around the outlook. Staff is closely monitoring the situation and will continue to work on assessing its impact and the related policy response in PNG and globally.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet